2006
DOI: 10.1111/j.1365-313x.2006.02674.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the integral membrane protein topology in living cells

Abstract: SummaryThe bimolecular fluorescence complementation (BiFC) phenomenon has been successfully applied for in vivo protein-protein interaction studies and protein tagging analysis. Here we report a novel BiFC-based technique for investigation of integral membrane protein topology in living plant cells. This technique relies on the formation of a fluorescent complex between a non-fluorescent fragment of the yellow fluorescent protein (YFP) targeted into a specific cellular compartment and a counterpart fragment at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
99
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(107 citation statements)
references
References 40 publications
6
99
0
2
Order By: Relevance
“…However, highly specific interactions between membrane proteins have been demonstrated using this technique in other systems (26)(27)(28). Also, the absence of an interaction with the plasma membrane protein PIP2-1 makes this possibility unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…However, highly specific interactions between membrane proteins have been demonstrated using this technique in other systems (26)(27)(28). Also, the absence of an interaction with the plasma membrane protein PIP2-1 makes this possibility unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…Most BiMC studies have focused on soluble proteins, although several have examined interactions of integral membrane proteins (30)(31)(32). One problem that is mentioned in these reports is where to place the tag.…”
Section: Discussionmentioning
confidence: 99%
“…from cell transformation to microscopy analyses), BiFC may introduce elements that lead to events that do not reflect normal cell physiology and these must be considered for correct interpretation of the results. Another point to consider is that in conditions of elevated availability of the YFP halves, YFP molecules may be generated simply because YFP halves tend to associate (Zamyatnin et al, 2006). It has also been reported that overexpression in mam- malian cells of N-and C-terminal YFP peptides alone resulted in a low fluorescence emission signal; thus, the levels of expression of the split-YFP halves may be a factor to consider in BiFC experiments (Ozalp et al, 2005).…”
Section: Split Yfpmentioning
confidence: 99%
“…Although this method is seemingly powerful, it may require careful controls to ensure that the disappearance of the fluorescence signal is not due to technical issues, such as photobleaching or excessive membrane permeabilization that may drastically alter the cell environment. Recently, Zamyatnin and colleagues demonstrated the usefulness of BiFC to determine membrane protein topology; model proteins used were the beet yellows virus-encoded p6 membrane-embedded movement protein, a protein with known topology, and the potato mop-top virus-encoded integral membrane TGBp2 protein with predicted topology (Zamyatnin et al, 2006). This application is based on the property of free split-YFP fragments to associate in plant cells as a result of their overexpression from strong promoters (Walter et al, 2004).…”
Section: Split Yfpmentioning
confidence: 99%